Impacts of spills on water quality and treatment plants: A case study using hydrodynamic and water quality modeling in the Nile River, Egypt - Amal Magdy; Elsayed Ramadan; Ahmed Moussa; Abdelazim Negm (Marine Pollution Bulletin, 2026)

Evaluating the impact of quality control deficiencies on asphalt concrete mix performance - Ali Qabur; ElSayed Adel Fahmy; Ahmed M. Youssef; Magdy Shaheen; Mohammed Samir Eisa; Khaled Aati; Rouba Joumblat (Innovative Infrastructure Solutions, 2026)

The nanocomposite of chitosan-vitamin C modulates the expression of immune and antioxidant-related genes in Nile tilapia stressed with lead (Pb) - Ahmed H. Sherif; Amr Fadel; Enas A. Kasem; Magdy E. Mahfouz; Elsayed A. Eldessouki; Hanan A. Fahmy (Aquaculture International, 2025)
Fish cultivated in a polluted environment usually face complicated disease cases. Pollution is an evitable event in aquaculture that weakens surface immunity, delaying and lowering the immune responses of aquatic animals. In an indoor experiment, Nile tilapia were reared in water polluted with lead (Pb) at a concentration of 51 µg/l for 8 weeks. A trial was conducted to mitigate the immunosuppression using pre-acclimatized Nile tilapia that were subdivided into six groups in which the exposed fish treated with nanocomposite (chitosan-vitamin C-protected nanoparticles (CVC-NPs)) consisted of 1 g of chitosan nanoparticles containing 400 mg vitamin C/kg fish and 200 mg vitamin C/kg fish feed for 1 week. Fish exposed to Pb pollution were immunocompromised as gene expression of immune-related cytokine and antioxidant enzymes significantly declined. Innate immunity was drastically impacted as OBA, phagocytosis and serum antibacterial activity (SAA) showed low values compared to the control fish; meanwhile, exposed fish was challenged against Streptococcus agalactiae and showed a high mortality rate (MR%). Dietary nanocomposite could restore normal immune status, and supplemented fish achieved low MR% with significantly high gene expression of proinflammatory cytokines. It was concluded that adding 200 mg of CVC-NPs/kg fish feed for 1 week could effectively protect Nile tilapia from S. agalactiae , having superiority over the high dose of 400 mg of CVC-NPs.

Promoting effect of sunset yellow on N-methyl N-nitrosourea-induced rat mammary carcinogenesis: Implications of molecular mechanisms - Elsayed I. Salim; Malak I. Elbassuny; Magdy E. Mahfouz; Eman M. El Nashar; Maha A. Alghamdi; Mohammad El-Nablaway; Hend M. Selim (Toxicology Letters, 2024)

Rosuvastatin repurposing for prophylaxis against ethanol-induced acute gastric ulceration in rats: a biochemical, histological, and ultrastructural perspective - Hanan I. El-kerdasy; Eman Mohamed Faruk; Dina Allam Abdelmaksoud Hassan; Ola Elsayed Nafea; Fatma Ibrahim; Rania Abubaker Bagabir; Hala Magdy Anwer; Amany M. Allam (Inflammopharmacology, 2024)

Adipose-Derived Mesenchymal Stem Cells and Their Derived Epidermal Progenitor Cells Conditioned Media Ameliorate Skin Aging in Rats - Omar I. Badr; Aya Anter; Ihab Magdy; Marvellous Chukueggu; Moamen Khorshid; Mohamed Darwish; Mohamed Farrag; Menna Elsayed; Youmna Amr; Yomna Amgad; Tasnim Mahmoud; Mohamed M. Kamal (Tissue Engineering and Regenerative Medicine, 2024)

Integration of hydrodynamic and water quality modeling to mitigate the effects of spill pollution into the Nile River, Egypt - Elsayed M. Ramadan; Ahmed Moussa; Amal Magdy; Abdelazim Negm (Environmental Science and Pollution Research, 2024)

Fabrication and optimization of itraconazole-loaded zein-based nanoparticles in coated capsules as a promising colon-targeting approach pursuing opportunistic fungal infections - Shery Adel; Rania H. Fahmy; Ibrahim Elsayed; Magdy I. Mohamed; Reem R. Ibrahim (Drug Delivery and Translational Research, 2023)
Itraconazole (ITZ), a broad-spectrum antifungal drug, was formulated into colon-targeting system aiming to treat opportunistic colonic fungal infections that commonly infect chronic inflammatory bowel diseases (IBD) patients due to immunosuppressive therapy. Antisolvent precipitation technique was employed to formulate ITZ-loaded zein nanoparticles (ITZ-ZNPs) using various zein: drug and aqueous:organic phase ratios. Central composite face-centered design (CCFD) was used for statistical analysis and optimization. The optimized formulation was composed of 5.5:1 zein:drug ratio and 9.5:1 aqueous:organic phase ratio with its observed particle size, polydispersity index, zeta potential, and entrapment efficiency of 208 ± 4.29 nm, 0.35 ± 0.04, 35.7 ± 1.65 mV, and 66.78 ± 3.89%, respectively. ITZ-ZNPs were imaged by TEM that revealed spherical core–shell structure, and DSC proved ITZ transformation from crystalline to amorphous form. FT-IR showed coupling of zein NH group with ITZ carbonyl group without affecting ITZ antifungal activity as confirmed by antifungal activity test that showed enhanced activity of ITZ-ZNPs over the pure drug. Histopathological examination and cytotoxicity tests ensured biosafety and tolerance of ITZ-ZNPs to the colon tissue. The optimized formulation was then loaded into Eudragit S100-coated capsules and both in vitro release and in vivo X-ray imaging confirmed the success of such coated capsules in protecting ITZ from the release in stomach and intestine while targeting ITZ to the colon. The study proved that ITZ-ZNPs is promising and safe nanoparticulate system that can protect ITZ throughout the GIT and targeting its release to the colon with effectual focused local action for the treatment of colon fungal infections. Graphical Abstract

Effects of dietary supplementation of chromium methionine chelate on growth performance, oxidative stress, hematological indices, and carcass traits of broiler chickens - Ibrahim M. I. Youssef; Ibrahim M. I. Abdo; Hassan F. A. Elsukkary; Magdy F. El-Kady; Magdy Elsayed (Tropical Animal Health and Production, 2022)
This study was conducted to evaluate the dietary effects of chromium methionine (Cr-Meth) chelate on growth performance, oxidative stress parameters, blood biochemistry, and carcass traits of broiler chickens. An experiment was conducted on 34,000 1-day-old straight-run broiler chicks (Indian River; 42.0 ± 0.03) at a commercial farm. The chicks were divided randomly into 3 groups; the first group contained 17,000 birds, which used as a control, whereas the second and third groups consisted of 7000 and 10,000 birds, respectively, with 5 replicates per group. A completely randomized design was used. The birds were fed the experimental diets containing graded levels of Cr-Meth chelate: 0 (control), 50, and 100 g/ton. This compound consisted of chromium (0.4%) chelated with methionine, and it supply the diets with 200 and 400 ppb Cr for the used levels of 50 and 100 g/ton feed, respectively. Growth performance indices (body weight, body weight gain, feed intake, and feed conversion ratio) were measured throughout the experiment. At the end of experiment, 10 birds per treatment were slaughtered, and the carcass yield with relative weight of the internal organs was determined. Also, blood samples were taken and analyzed for glutathione peroxidase activity, malondialdehyde, ALT, AST, total protein, albumin, glucose, urea, creatinine, triglycerides, and total cholesterol. It was found that Cr-Meth improved the body weight, weight gain, feed intake, and feed conversion ratio of broilers. Moreover, it reduced the mortality rate of birds. The chelated chromium can alleviate the oxidative status of birds by increasing the plasma glutathione peroxidase activity and reducing the serum malondialdehyde level. It was observed that the effects of 100 g/ton Cr-Meth chelate on performance indices, mortality rate, and oxidative stress parameters were better than that of 50 g/ton inclusion rate. Supplementation of Cr-Meth increased the total protein level, but reduced the glucose, total cholesterol, and triglyceride concentrations in the blood serum. In addition, it increased the carcass yield and reduced the abdominal fat percentage of the birds’ carcass. Therefore, chromium can be included in diets of broilers at a rate of 200 to 400 ppb, and the higher concentration was more effective than the lower one. So, it can be recommended to use Cr-Meth chelate in broiler diets at 100 g/ton to improve the productive performance and reduce the oxidative stress of birds.

Onset of feeding in juvenile sea urchins and its relation to nutrient signalling - Alyaa Elsaid Abdelaziz Fadl; Magdy Elsayed Mahfouz; Mona Mabrouk Taha El-Gamal; Andreas Heyland (Invertebrate Reproduction & Development, 2019)

Synthesis and characterization of some chelating polymers bearing maleic acid and/or sodium maleate moieties for removal of some toxic heavy metal ions - Mahmoud Abd El-Ghaffar; Noha Elhalawany; Elsayed Ahmed; Magdy Sabaa (Clean Technologies and Environmental Policy, 2013)